Equivalence in Bilingual Lexicography: Criticism and Suggestions - Wiegand, Herbert Ernst (Lexikos, 2002)
Abstract: A reminder of general problems in the formation of terminology, as illustrated by theGerman Äquivalence (Eng. equivalence) and äquivalent (Eng. equivalent), is followed by a critical discussionof the concept of equivalence in contrastive lexicology. It is shown that especially the conceptof partial equivalence is contradictory in its different manifestations. Consequently attemptsare made to give a more precise indication of the concept of equivalence in the metalexicography,with regard to the domain of the nominal lexicon. The problems of especially the metalexicographicconcept of partial equivalence as well as that of divergence are fundamentally expounded.In conclusion the direction is indicated to find more appropriate metalexicographic versions of theconcept of equivalence. Keywords: EQUIVALENCE, LEXICOGRAPHIC EQUIVALENT, PARTIAL EQUIVALENCE,CONGRUENCE, DIVERGENCE, CONVERGENCE, POLYDIVERGENCE, SYNTAGM-EQUIVALENCE,ZERO EQUIVALENCE, CORRESPONDENCE Abstrakt: Äquivalenz in der zweisprachigen Lexikographie: Kritik und Vorschläge.Nachdem an allgemeine Probleme der Begriffsbildung am Beispiel von dt. Äquivalenzund dt. äquivalent erinnert wurde, wird zunächst auf Äquivalenzbegriffe in der kontrastiven Lexikologiekritisch eingegangen. Es wird gezeigt, dass insbesondere der Begriff der partiellen Äquivalenzin seinen verschiedenen Ausprägungen widersprüchlich ist. Sodann werden Präzisierungenzu den Äquivalenzbegriffen in der Metalexikographie versucht, die sich auf den Bereich der Nennlexikbeziehen. Insbesondere der metalexikographische Begriff der partiellen Äquivalenz sowie derder Divergenz werden grundsätzlich problematisiert. In welche Richtung man gehen kann, umangemessenere metalexikographische Fassungen des Äquivalenzbegriffs zu finden, wird abschließendangedeutet. Stichwörter: ÄQUIVALENZ, LEXIKOGRAPHISCHES ÄQUIVALENT, PARTIELLE ÄQUIVALENZ,KONGRUENZ, DIVERGENZ, KONVERGENZ, POLYDIVERGENZ, SYNTAGMENÄQUIVALENZ,NULLÄQUIVALENZ, KORRESPONDENZ